Post-Translational Modifications of Histones in Human Sperm - Krejčí, Jana; Stixová, Lenka; Pagáčová, Eva; Legartová, Soňa; Kozubek, Stanislav; Lochmanová, Gabriela; Zdráhal, Zbyněk; Sehnalová, Petra; Dabravolski, Siarhei; Hejátko, Jan; Bártová, Eva (Journal of cellular biochemistry, 2015)
We examined the levels and distribution of post-translationally modified histones and protamines in human sperm. Using western blot immunoassay, immunofluorescence, mass spectrometry (MS), and FLIM-FRET approaches, we analyzed the status of histone modifications and the protamine P2. Among individual samples, we observed variability in the levels of H3K9me1, H3K9me2, H3K27me3, H3K36me3, and H3K79me1, but the level of acetylated (ac) histones H4 was relatively stable in the sperm head fractions, as demonstrated by western blot analysis. Sperm heads with lower levels of P2 exhibited lower levels of H3K9ac, H3K9me1, H3K27me3, H3K36me3, and H3K79me1. A very strong correlation was observed between the levels of P2 and H3K9me2. FLIM-FRET analysis additionally revealed that acetylated histones H4 are not only parts of sperm chromatin but also appear in a non-integrated form. Intriguingly, H4ac and H3K27me3 were detected in sperm tail fractions via western blot analysis. An appearance of specific histone H3 and H4 acetylation and H3 methylation in sperm tail fractions was also confirmed by both LC-MS/MS and MALDI-TOF MS analysis. Taken together, these data indicate that particular post-translational modifications of histones are uniquely distributed in human sperm, and this distribution varies among individuals and among the sperm of a single individual.
Keywords: sekvence aminokyselin; histonmethyltransferasy; lidé; metylace; mužské pohlaví; EPIGENETICS; posttranslační úpravy proteinů; Chromatin; histony; Histones; Protein Processing, Post-Translational; Humans; Amino Acid Sequence; Tandem Mass Spectrometry; MICROSCOPY; acetylace; HUMAN SPERM; histonlysin-N-methyltransferasa; Histone-Lysine N-Methyltransferase; tandemová hmotnostní spektrometrie; chromatin; PROTAMINE P2; Acetylation; Spermatozoa; HISTONES; Methylation; Histone Methyltransferases; spermie; Male